2018
DOI: 10.5194/angeo-36-1153-2018
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic auroras near the geomagnetic equator: in the Philippines, on 27 October 1856

Abstract: Abstract. While low-latitude auroral displays are normally considered to be a manifestation of magnetic storms of considerable size, Silverman (2003, JGR, 108, A4) reported numerous “sporadic auroras” which appear locally at relatively low magnetic latitude during times of just moderate magnetic activity. Here, a case study is presented of an aurora near the geomagnetic equator based on a report from the Philippine islands on 27 October 1856. An analysis of this report shows it to be consistent with the known … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 69 publications
(100 reference statements)
1
11
0
Order By: Relevance
“…The aurora description presented by Liais is consistent with sporadic aurorae (Abbe, 1895;Botley, 1963;Silverman, 2003). In addition, the very low magnetic latitude of Rio de Janeiro and the weak/mild magnetic activity during the observations are consistent with a previous sporadic aurora observation near the magnetic equator (Hayakawa, Vaquero, & Ebihara, 2018).…”
Section: Conclusion and A Final Remarksupporting
confidence: 87%
See 2 more Smart Citations
“…The aurora description presented by Liais is consistent with sporadic aurorae (Abbe, 1895;Botley, 1963;Silverman, 2003). In addition, the very low magnetic latitude of Rio de Janeiro and the weak/mild magnetic activity during the observations are consistent with a previous sporadic aurora observation near the magnetic equator (Hayakawa, Vaquero, & Ebihara, 2018).…”
Section: Conclusion and A Final Remarksupporting
confidence: 87%
“…Silverman (2003) provided a survey of considerable sporadic aurora observations in low-latitude regions of the United States during a time span of over half a century, and highlighted the occurrence of sporadic aurorae in the context of mid-to low-latitude aurorae during moderate to low magnetic activity. That paper was later followed by other papers with reports on sporadic aurora sightings from Iberia and the Canary Islands (Vaquero, Trigo, & Gallego, 2007;Vázquez & Vaquero, 2010), East Asia (Willis, Stephenson, & Fang, 2007), Mexico (Vaquero, Gallego, & Domínguez-Castro, 2013), and the Philippines (Hayakawa, Vaquero, & Ebihara, 2018). Interestingly, Shiokawa et al (2005) reported three cases of instrumental observations of mid-latitude aurora in Hokkaido (Japan) under fairly moderate magnetic activity as well.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…During this stormy interval, 9 records are found to contain information about the elevation angle of the aurora as listed in Table 1. Assuming the height of the upper border of the aurora, we estimate the equatorward boundary of the auroral emission region on the basis of the geometry of the dipole magnetic field line as shown in Figure 2 (See also Hayakawa et al (2018c)). We also assume that (1) the aurora is very thin in the latitudinal direction and is extended along a dipole magnetic field line, and that (2) atmospheric refraction is negligible.…”
Section: Estimation Of Equatorward Boundary Of Auroral Emission Regionmentioning
confidence: 99%
“…Silverman (2003) reviewed these aurorae and named them "sporadic aurorae" (Silverman, 2003), setting its threshold in daily aa index as ≤55 (Silverman, 2003; see also Willis et al, 2007). They are generally faint aurorae, while their physical properties such as duration and relationship with substorms are currently under further investigations (Silverman, 2003;cf., e.g., Akasofu, 1964;Hayakawa, Vaquero, & Ebihara, 2018;Oliveira et al, 2020). Although their physical mechanism has not been fully understood, follow-up works have recovered such sporadic aurorae in other middle-to low-latitude regions (Hayakawa, Vaquero, & Ebihara, 2018;Oliveira et al, 2020;Vaquero et al, 2007;Vauqero et al, 2013;Willis et al, 2007).…”
Section: Introductionmentioning
confidence: 99%